P.120 Case series: Clinical and genetic spectrum of SCN8A-related disorders in British Columbia. (November 2021) - Hebbar, M; Al-Taweel, N; Gill, I; Boelman, C; Dean, RA; Goodchild, SJ; Mezeyova, J; Shuart, NG; Johnson, JP; Lee, J; Michoulas, A; Huh, LL; et al.
Abstract : Background: Children with pathogenic variations in SCN8A can present with early infantile epileptic encephalopathy-13, benign familial infantile seizures-5 or intellectual disability alone without epilepsy. In this case series, we discuss six children with variants in SCN8A managed at BC Children's Hospital. Methods: We describe clinical and genetic results on six individuals with SCN8A variants identified via clinical or research next-generation sequencing. Functional consequences of two SCN8A variants were assessed using electrophysiological analyses in transfected cells. Results: Clinical findings ranged from normal development with well-controlled epilepsy to significant developmental delay with treatment-resistant epilepsy. Phenotypes and genotypes in our cohort are described in the table below. Functional analysis supported gain-of-function in P2 and loss-of-function in P4. Conclusions: Our cohort expands the clinical and genotypic spectrum of SCN8A-related disorders. We establish functional evidence for two missense variants in SCN8A, including LoF variant in a patient with intellectual disability, and autism spectrum disorder without seizures.